Odpowiedź :
[tex]zad.1\\\\a)~~x^{2} +4x=0\\\\x\cdot (x+4)=0\\\\x=0~~\lor~~x+4=0\\\\x=0~~\lor~~x=-4\\\\b)~~x^{2} -0,5x=0\\\\x\cdot (x-0,5)=0\\\\x=0~~\lor~~x-0,5=0\\\\x=0~~\lor~~x=0,5\\\\c)~~x^{2} -1,2x=0\\\\x\cdot (x-1,2)=0\\\\x=0~~\lor~~x-1,2=0\\\\x=0~~\lor~~x=1,2\\\\d)~~x^{2} +\dfrac{2}{3} x=0\\\\x\cdot ( x +\dfrac{2}{3} )=0\\\\x=0~~\lor~~x+\dfrac{2}{3} =0\\\\x=0~~\lor~~x=-\dfrac{2}{3} \\\\[/tex]
[tex]e)~~x^{2} +ax=0\\\\x\cdot (x+a)=0\\\\x=0~~\lor~~x+a=0\\\\x=0~~\lor~~x=-a\\\\f)~~2x^{2} +bx=0\\\\x\cdot (2x+b)=0\\\\x=0~~\lor~~2x+b=0\\\\x=0~~\lor~~x=-\dfrac{1}{2} b\\\\g)~~3x^{2} =3ax~~\mid~~\div 3\\\\x^{2} =ax\\\\x^{2} -ax=0\\\\x\cdot (x-a)=0\\\\x=0~~\lor~~x-a=0\\\\x=0~~\lor~~x-a=0\\\\x=0~~\lor~~x=a\\\\h)~~ax^{2} -2ax=0~~,a\neq 0\\\\ax^{2} -2ax=0~~\mid~~\div a\\\\x^{2} -2x=0\\\\x\cdot (x-2)=0\\\\x=0~~\lor~~x-2=0\\\\x=0~~\lor~~x=2[/tex]